The Creative Process in Traiettoria : An Account of the Genesis of Marco Stroppa's Musical Thought. - Tiffon, Vincent; Sprenger-Ohana, Noémie (Contemporary Music Review, 2011)
This paper aims to explore Marco Stroppa's compositional workshop through the emblematic work Traiettoria to demonstrate how an underlying trend of spectral thought was present in the composer's mind during the gestation of the work but did not determine his aesthetic orientation. From the study of common filiations and difference between Marco Stroppa and the spectral composers, we intend to show how his years of intensive training in various disciplines crystallise into Traiettoria , giving rise to personal and long-lasting key concepts.